Effects of Zinc Chloride Impregnation on the Characteristics of Activated Carbon Produced from Physic Nut Seed Hull - Yakub, I.; Mohammad, M.; Yaakob, Z. (Trans Tech Publications, Switzerland, 2013)
Activated carbon was developed from physic nut seed hull through chemical activation using zinc chloride. The characteristics of raw physic nut seed hull as well as char and activated carbon from physic nut seed hull were obtained to study the effects of ZnCl2 impregnation. The comparisons of the characteristics that included elemental composition, surface morphology, surface area, surface functional groups and zeta potential were made on the three samples. The study found that ZnCl2 had positive effects towards developing activated carbon including increasing the carbon content, surface area and pore volume besides improving the microporosity and surface charge distribution of the carbon.